Formulation and Evaluation of Chronomodulated Press-coated Tablets of Tapentadol HCl - Pati, Nikunja B. (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: Press-coated tablets of Tapentadol HCl are proposed to achieve the release of drug after a programmable period of time. It is intended to be used mainly in the therapy of those diseases and symptoms which depend on circadian rhythms like many pain conditions. Methods: A core formulation containing Tapentadol hydrochloride as model drug is coated by compression with different polymeric barrier layers (press-coated systems) in different weight ratios. The core serves as a reservoir, and the release-controlling layer protect the core from the environment, e.g., water, acidic pH, and enzymes until the drug is released after a predetermined lag phase. The coatings can erode/dissolve, rupture or alter their permeability at the required time. The shell formulations tested contained erodible polymers. The dissolution profiles of uncoated cores and press-coated devices were compared. The coating is expected to prevent drug release from the core until the polymeric shell is completely eroded or swollen. Nine formulations were prepared and evaluated for various parameters. Results: Formulation F3, F4, and F6 possessed good lag time 4–4.5 h and showed pulsatile drug delivery pattern. Except for the time-lag, the release kinetics of the drug contained in the core were not significantly influenced by the presence of the erodible barrier but can be widely be modulated using a swellable polymeric shell. Conclusion: Results of the study indicated that floating - press-coated based pulsatile release formulations are suitable for Tapentadol hydrochloride.